2020
DOI: 10.3390/nu12082483
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Release after Simulated Infant In Vitro Digestion of Dry Heated Cow’s Milk Protein and Transport of Potentially Immunoreactive Peptides across the Caco-2 Cell Monolayer

Abstract: Dry heating of cow’s milk protein, as applied in the production of “baked milk”, facilitates the resolution of cow’s milk allergy symptoms upon digestion. The heating and glycation-induced changes of the protein structure can affect both digestibility and immunoreactivity. The immunological consequences may be due to changes in the peptide profile of the digested dry heated milk protein. Therefore, cow’s milk protein powder was heated at low temperature (60 °C) and high temperature (130 °C) and applied to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In the emulsion system, by introducing negatively charged phosphate groups, the droplets gain a strong electrostatic repulsive force, which improves the surface charge intensity of the droplets. This leads to better spatial stability and prevents aggregation and coalescence between the droplets [23,27,28]. For samples with reduced zeta potential, this may be attributed to the formation of aggregates, because the decrease in surface charge may be related to the exposure of hydrophobic non-polar residues through the expansion of the tertiary structure.…”
Section: Element Content and Zeta Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In the emulsion system, by introducing negatively charged phosphate groups, the droplets gain a strong electrostatic repulsive force, which improves the surface charge intensity of the droplets. This leads to better spatial stability and prevents aggregation and coalescence between the droplets [23,27,28]. For samples with reduced zeta potential, this may be attributed to the formation of aggregates, because the decrease in surface charge may be related to the exposure of hydrophobic non-polar residues through the expansion of the tertiary structure.…”
Section: Element Content and Zeta Potentialmentioning
confidence: 99%
“…With the increasing negative charges introduced by phosphate groups along the protein molecular surface, the hydration of protein will be enhanced and lead to the improvement in water solubility [8,24]. The phosphorylation of the lysine site in gelatin hinders the hydrolysis of lysine residues in gelatin and reduces the content of lysine, so the content of amino acids is reduced [28]. The three kinds of fish scale gelatins had different reduction rules of amino acids, which was due to different degrees of phosphorylation reaction.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…For example, it has been shown that lysine blockage induced a significant change in the peptide pattern after simulated infant gastrointestinal digestion. 6 Heat treatment reduced significantly available lysine of skim milk powder measured in growing rats. [7][8][9] However, the effect of thermal processing on protein digestibility is still controversial since protein denaturation may enhance digestibility by the exposure new cleavage sites to the action of the digestive enzymes, but protein aggregation and glycation impairs protein digestibility.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, differentiated Caco-2 monolayers display cell polarization, microvillus structure, carrier-mediated transport systems and tight junctions, and are therefore considered well suited for studies of intestinal uptake [6,7]. In vitro studies have shown that bioactive milk peptides can cross Caco-2 monolayers, e.g., ACE-inhibitory peptides from β-lactoglobulin and whey hydrolysates [8,9], IgE immunoreactive peptides from simulated infant digestion [10], the opioid peptides β-casomorphin-5 and β-casomorphin-7 [11], two anxiolytic peptides from αs 1 -casein [12] and a 17 residue immunomodulatory peptide from β-casein [13]. In vivo, the caseinomacropeptide (residues 106-169 of κ-casein) has been detected in plasma from newborns after breastfeeding and formula feeding, as well as in adult plasma after milk or yogurt ingestion [14,15].…”
Section: Introductionmentioning
confidence: 99%